2016
DOI: 10.15405/ejsbs.180
|View full text |Cite
|
Sign up to set email alerts
|

Online Gaming Behavior And Psychosocial Well-Being In Greek Adolescents

Abstract: Online gaming is an appealing and popular activity among adolescents. However, several studies have shown that excessive engagement is related to psychosocial problems. The present study is based on data from the EU NET ADB project and examined the association between problematic online gaming and psychosocial wellbeing in a Greek school-student's sample. Problematic online gaming is classified in the DSM-5 as Internet Gaming Disorder (IGD) and was measured with the Assessment of Internet and Computer game Add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…It was found that happiness level was negatively associated with the gaming disorder level. When the literature was examined, it was seen that similar results were obtained [54][55][56]59,[61][62][63][64][65][66]. Happiness is associated with meeting an individual's need for approval in life.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…It was found that happiness level was negatively associated with the gaming disorder level. When the literature was examined, it was seen that similar results were obtained [54][55][56]59,[61][62][63][64][65][66]. Happiness is associated with meeting an individual's need for approval in life.…”
Section: Discussionmentioning
confidence: 71%
“…The studies determined a positive relationship between technology addiction-related gaming disorder and narcissism [15][16][17][18]53]. Moreover, some studies found a negative relationship between gaming disorder and happiness [54][55][56][57][58][59][60][61][62][63][64][65][66]. In contrast, some found a positive relationship between gaming disorder and happiness levels [67].…”
Section: Gaming Disorder Narcissism and Happiness And The Present Researchmentioning
confidence: 99%
“…The third criteria is psychology. Online game addiction is a Millenials' psychosocial problem, including students [18]. Children who have quality friendships have a low risk of game addiction, while children who have social anxiety and loneliness fall to the high-risk game addiction [19].…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have shown IGD to be associated with loneliness ( Wang, Sheng, & Wang, 2019 ), anxiety ( Wang et al., 2017 ), depression ( Wang, Cho, & Kim, 2018 ), lower academic achievement ( Hawi, Samaha, & Griffiths, 2018 ), conduct problem ( Brunborg, Mentzoni, & Frøyland, 2014 ), sleep difficulties ( Wong et al., 2020 ), and lower psychosocial well-being ( Pappa, Apergi, Ventouratou, Janikian, & Beratis, 2016 ). Decreased physical activity ( Henchoz et al., 2016 ) and physical symptoms, such as pain in the wrist joints, were also found to be significantly associated with IGD ( Gentile, 2009 ).…”
Section: Introductionmentioning
confidence: 99%
“…To achieve this goal, it is necessary to distinguish between the risk factors that cause IGD and the outcomes of IGD. However, most previous studies including those mentioned above on the association between IGD, sleep, physical activity, and physical symptoms have been based on cross-sectional designs ( Cankurtaran et al., 2022 ; Gentile, 2009 ; Henchoz et al., 2016 ; Lee et al., 2019 ; Mukhra et al., 2019 ; Pappa et al., 2016 ; Wong et al., 2020 ). Therefore, it provides insufficient evidence for temporal relationships and to infer causal relationships.…”
Section: Introductionmentioning
confidence: 99%